2020
DOI: 10.1093/mnras/staa233
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary status of protostellar clumps hosting class II methanol masers

Abstract: The Methanol MultiBeam survey (MMB) provides the most complete sample of Galactic massive young stellar objects (MYSOs) hosting 6.7 GHz class II methanol masers. We characterise the properties of these maser sources using dust emission detected by the Herschel Infrared Galactic Plane Survey (Hi-GAL) to assess their evolutionary state. Associating 731 (73%) of MMB sources with compact emission at four Hi-GAL wavelengths, we derive clump properties and define the requirements of a MYSO to host a 6.7 GHz maser. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 99 publications
(193 reference statements)
4
4
2
Order By: Relevance
“…The mean temperature of a maser clump is 23.9 K whereas the mean temperature of an ATLASGAL clump is 19.4 K. We have also tested the samples using a KS test and find that the differences in temperature between the two samples is statistically significant (p 0.0013). This difference has also been noted in another previous study by Jones et al (2020), who examined a sample of 731 MMB sources with compact emission at four Hi-GAL wavelengths, and investigated the association between masers and Hi-GAL sources.…”
Section: Physical Parameterssupporting
confidence: 69%
See 1 more Smart Citation
“…The mean temperature of a maser clump is 23.9 K whereas the mean temperature of an ATLASGAL clump is 19.4 K. We have also tested the samples using a KS test and find that the differences in temperature between the two samples is statistically significant (p 0.0013). This difference has also been noted in another previous study by Jones et al (2020), who examined a sample of 731 MMB sources with compact emission at four Hi-GAL wavelengths, and investigated the association between masers and Hi-GAL sources.…”
Section: Physical Parameterssupporting
confidence: 69%
“…The mean and median luminosities for maser associated clumps are both ∼10 4 L . These values are ∼ 2 times higher than those found by Jones et al (2020), likely due to the differences in the way that the luminosity measurements were conducted. This implies that a certain protostellar luminosity is required, and therefore, protostellar mass in order to drive sufficient Table 5.…”
Section: Physical Parameterscontrasting
confidence: 56%
“…The mean and median luminosities for maser associated clumps are both ∼10 4 L . These values are ∼ 2 times higher than those found by Jones et al (2020), likely due to the differences in the way that the luminosity measurements were…”
Section: Physical Parameterscontrasting
confidence: 56%
“…Studies have also investigated the relationship between different maser species (e.g. Forster & Caswell 1989;Menten 1997;Szym-czak et al 2005;Jones et al 2020), and it has been shown that different maser transitions are often spatially associated with one another (within 15 arcsec). Ellingsen et al (2007) presented a "straw man" model for the evolution and relative timescales of different maser species (water, methanol, hydroxyl) within regions of star formation.…”
mentioning
confidence: 99%
“…EGOs are also strongly associated both with radiatively-pumped 6.7 GHz Class II CH 3 OH masers, which are known to exclusively trace high-mass star formation (e.g. Cragg et al 2005;Billington et al 2019;Jones et al 2020), and with collisionally-pumped 44 and 25 GHz Class I CH 3 OH masers (e.g. Cyganowski et al 2008Cyganowski et al , 2009Towner et al 2017).…”
Section: Introductionmentioning
confidence: 99%